I06 Correlations between structural damage and functional deficits in early Huntington's disease. (16th November 2010) - Delmaire, C; Dumas, E M; Sharman, M; van den Bogaard, S J A; Valabregue, R; Jauffret, C; Reilmann, R; Stout, J C; Craufurd, D; Tabrizi, S J; Roos, R A C; Lehéricy, S; et al.
Abstract : Background: It is likely that clinical deficits in Huntington's disease (HD) arise from damage involving a cortico-basal ganglia network rather than damage in the striatum only. Aims: To determine the structural correlates of impaired brain functions in HD by using whole brain voxel based DTI analysis. Methods: DTI axial slices were obtained using a 3T system (slice thickness 2 mm no gap, 50 independent directions). We included 24 early HD and 23 controls from the TRACK-HD Paris site cohort. Voxelwise group comparisons of white matter fractional anisotropy (FA) and mean diffusivity (MD) were performed using voxel based analysis (SPM5, clusters considered significant at p<0.05, corrected for multiple comparisons). We selected one task in each cognitive domain which showed significant cross-sectional differences at baseline: motor (self-paced tapping tasks), cognitive (UPSIT), attention (Trail B making test) and behavioural (Apathy scores calculated from problem behaviours assessment). Results: There was a significant decrease in FA in several white matter association pathways and increase in FA in the anterior putamen. Voxel based MD analysis showed a diffuse increase in MD in cortical grey, white matters and in the basal ganglia. There were significant correlations between: (i) self-paced tapping and MD in the parietal gyrus at 1.8 Hz and the prefrontal areas at 3 Hz, (ii) UPSIT test and MD in the parietal and occipital lobes, the cingulum and the insula, and FA in the insular and external capsule white matter, (iii) TMT tests and diffusion in the frontal, temporal gyri, the superior parietal and the post central gyri and (iv) apathy and FA in the rectus gyrus bilaterally. Conclusions: Disruption of motor, associative and limbic cortico-striatal circuits differentially contribute to the clinical signs of the disease and play a role in symptom development.